Research trends on flipped classrooms of mathematics creative thinking, critical thinking, and problem-solving skills - Muhammad Fayakuun; Arief Agoestanto (Jurnal Elemen, 2023)
Some studies discussed learning outcomes, challenges, and the effect of media learning on flipped classrooms of mathematics creative thinking (MCeT), critical thinking (MCiT), and problem-solving (MPS) skills. None of the studies reviewed the research information. This study aimed to examine trend research by year and the diversity of research methods, quantitative research designs, research subjects, mathematics topics, research variables, data collection tools, test designs, data analysis methods, and learning media in articles published in Scopus,  Education Resources Information Centre (ERIC), and Garba Rujukan Digital (Garuda) databases of mathematics educational journals from January 2018 to April 2023. The method of this study was the content analysis method. Twenty-two articles were evaluated in this study. The results showed that the research trend by year was increasing. The most type of research methods, quantitative research design, research subjects, mathematics topic, research variables, data collecting tools, kind of test design, data analysis techniques, and learning media were quasi-experimental design, eighth-grade junior high school students, three-dimensional shape, problem-solving, test sheet, pretest-posttest, t-test, and video, respectively. This study gave insights to other researchers for future decision-making on flipped classrooms of MCeT, MCiT, and MPS skills.